2016
DOI: 10.1002/2016gl069233
|View full text |Cite
|
Sign up to set email alerts
|

Geographical, seasonal, and depth variation in sinking particle speeds in the North Atlantic

Abstract: Particle sinking velocity is considered to be a controlling factor for carbon transport to the deep sea and thus carbon sequestration in the oceans. The velocities of the material exported to depth are considered to be high in high‐latitude productive systems and low in oligotrophic distributions. We use a recently developed method based on the measurement of the radioactive pair 210Po‐210Pb to calculate particle sinking velocities in the temperate and oligotrophic North Atlantic during different bloom stages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 46 publications
11
41
1
Order By: Relevance
“…The Martin curve is equivalent to a decreasing remineralization rate with depth or an increasing sinking speed with depth [ Lam et al , ]. Villa‐Alfageme et al [] observed an increase in sinking speed with depth, possibly due to the gradual loss of slow‐sinking particles with depth. Small values of b imply a higher transfer efficiency where more carbon remineralizes at deeper depths.…”
Section: Methodsmentioning
confidence: 99%
“…The Martin curve is equivalent to a decreasing remineralization rate with depth or an increasing sinking speed with depth [ Lam et al , ]. Villa‐Alfageme et al [] observed an increase in sinking speed with depth, possibly due to the gradual loss of slow‐sinking particles with depth. Small values of b imply a higher transfer efficiency where more carbon remineralizes at deeper depths.…”
Section: Methodsmentioning
confidence: 99%
“…There is substantial variation in particle sinking speed in the ocean because particle sizes vary over orders of magnitude (Alldredge & Silver, 1988;Villa-Alfageme et al, 2016) and particle sinking speed has been generally observed to increase as a power law function with particle size (Alldredge & Gotschalk, 1989;Smayda, 1971). For a given equivalent particle size, its shape and roughness can also influence sinking speed (Dietrich, 1982;Johnson et al, 1996).…”
Section: Particle Velocitymentioning
confidence: 99%
“…This result implies that a parameterization of particle SV with a Stokes' model could be more robust in the mesopelagic layer and deeper ocean. Increase of particle SV with depth (Berelson ; Trull et al ; Villa‐Alfageme et al ) could thus be potentially simulated through compositional changes in addition to depth‐varying size classes (SV strictly size‐dependent; Kriest and Oschlies ) or a prescribed linear SV increase with depth (Gehlen et al ; Kriest and Oschlies ; Aumont et al ).…”
Section: Concluding Remarks: Implications For Biogeochemical Model Pamentioning
confidence: 99%